1992
DOI: 10.1002/ijc.2910500616
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of hepatic uptake of a radiolabelled monoclonal antibody

Abstract: Clinical and experimental scintigraphic studies have found that radiolabelled antibodies are not only taken up by tumour(s) but also by normal liver. The accumulation of radionuclides in this organ poses a major problem to the use of radiolabelled antibodies as diagnostic and therapeutic tools. In an attempt to understand the mechanism of hepatic uptake and clearance of radiolabelled antibodies, the intrahepatic biodistribution of an 111In-labelled MAb (HMFG1), was determined following i.v. administration to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Hepatic uptake of radiolabeled ING-1 was observed in keeping with previous studies with other monoclonal antibodies that have demonstrated that the liver can take up to 15% of the administered dose of radiolabeled antibody (47). It has been suggested that this is due to extravascular pooling of antibody and not antibody-antigen interactions, which is in keeping with the absence of induced transaminitis or hepatic toxicity in this clinical trial.…”
Section: Discussionsupporting
confidence: 89%
“…Hepatic uptake of radiolabeled ING-1 was observed in keeping with previous studies with other monoclonal antibodies that have demonstrated that the liver can take up to 15% of the administered dose of radiolabeled antibody (47). It has been suggested that this is due to extravascular pooling of antibody and not antibody-antigen interactions, which is in keeping with the absence of induced transaminitis or hepatic toxicity in this clinical trial.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, there was significantly higher accumulation of Miltuximab Âź -IR800 in the tumor when compared to the liver (p = 0.009) or kidneys (p = 0.011). We noted accumulation of systemically delivered monoclonal antibody in the liver for both Miltuximab Âź -IR800 and IgG-IR800 isotype control, as expected [46]. In the isotype control IgG-IR800, the uptake of the conjugates was found to be greater in the liver and kidney than in the tumor.…”
Section: Ex Vivo Fluorescence Of the Tumors And Major Organssupporting
confidence: 82%
“…The monoclonal antibody (mAb) HMFG1 binds to the linear core protein sequence, PDTR, contained within the immunodominant domain of the tandem repeats of MUC1 (Burchell and Taylor-Papadimitriou, 1993). HMFG1 has been used both to localize ovarian cancers by radioimmunoscintigraphy (Boyle et al, 1992) and for radiotherapy (Kosmas et al, 1998).…”
mentioning
confidence: 99%